A laicidade republicana em França ou os paradoxos de um processo histórico de laicização (séculos XVIII-XXI) - Valentine Zuber (Ler História, 2010)
French laity is the result of a historical process that makes it a possible way of secularization in modern societies. With the increasing plurality of beliefs and the relativity of values in the broader context of contemporary globalization, the French secularism finds new challenges in the traditional territories for action: the school and public sphere. This essay starts presenting the history of this particular process of secularization in France since French Revolution to the present, ending with a thematic analysis of the new challenges of French secularism and the debates it generates in nowadays society.